2017
DOI: 10.1017/wet.2017.64
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Southern US Rice Cultivars to Benzobicyclon

Abstract: Benzobicyclon is the first 4-hydroxyphenylpyruvate dioxygenase-inhibiting herbicide pursued for commercial registration in U.S. rice production. A study was conducted in 2015 and 2016 to evaluate the response of eight rice cultivars to post-flood application timings of benzobicyclon at 494 g ai ha-1(proposed 2X rate). ‘Caffey’, ‘CL151’, ‘CLXL745’, ‘Jupiter’, ‘LaKast’, ‘Mermentau’, ‘Roy J’, and ‘XL753’ were evaluated in response to applications of benzobicyclon. The highest level of visible injury was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
3
8
0
Order By: Relevance
“…As predicted, his1/his1 accessions/cultivars were highly sensitive to benzobicyclon at 371 g ha −1 regardless of growth stage, and predominantly HIS1 accessions or HIS1/HIS1 cultivars (e.g., LaKast) at the ≥5-leaf growth stage were tolerant. These statements are supported by evidence in the literature (Akasaka et al 2011;Kwon et al 2012;Lv et al 2021;Maeda et al 2019;Young et al 2017). For HIS1/his1 accessions/cultivars, the model predicted severe suppression to complete control at ≤2-leaf growth stage, which was observed at the Pine Tree location, but the model would indicate greater control at the 5-leaf growth stage.…”
Section: Weedy Rice Control Model and Proof Of Concept Experimentssupporting
confidence: 72%
“…As predicted, his1/his1 accessions/cultivars were highly sensitive to benzobicyclon at 371 g ha −1 regardless of growth stage, and predominantly HIS1 accessions or HIS1/HIS1 cultivars (e.g., LaKast) at the ≥5-leaf growth stage were tolerant. These statements are supported by evidence in the literature (Akasaka et al 2011;Kwon et al 2012;Lv et al 2021;Maeda et al 2019;Young et al 2017). For HIS1/his1 accessions/cultivars, the model predicted severe suppression to complete control at ≤2-leaf growth stage, which was observed at the Pine Tree location, but the model would indicate greater control at the 5-leaf growth stage.…”
Section: Weedy Rice Control Model and Proof Of Concept Experimentssupporting
confidence: 72%
“…Ducksalad control was 79% to 93% when treated with benzobicyclon at 246 to 1,232 g ha –1 (Table 2). Young et al (2016) observed 99% control of ducksalad, California arrowhead ( Sagittaria montevidensis Cham. & Schltdl.…”
Section: Resultsmentioning
confidence: 99%
“…Applications of benzobicyclon alone never resulted in more than 4% visible injury to rice, whereas visible injury following florpyrauxifen-benzyl alone ranged from 4 to 27% (Table 5). All lines tested for sensitivity in this study were not in possession of the HPPD inhibitor sensitive 1 gene; therefore, minimal injury was expected from a stand-alone application of benzobicyclon (Kwon et al, 2012;Young et al, 2017).…”
Section: Sensitivity To Florpyrauxifen-benzyl Followed By Benzobicyclonmentioning
confidence: 99%
“…Tolerance to benzobicyclon is known to differ between rice cultivars of japonica and indica origin (Kwon et al., 2012). Cultivars of japonica origin show little to no injury after application, whereas those of indica descent show as much as 98% injury 6 wk after application, with eventual death in some instances (Kwon et al., 2012; Young et al., 2017). Cultivar tolerance to benzobicyclon has been attributed to the presence of the HPPD inhibitor sensitive 1 gene, which is commonly found in cultivars of indica descent (Maeda et al., 2019).…”
Section: Introductionmentioning
confidence: 99%